+0  
 
0
467
1
avatar

why is root 3i multiplied by - root 3i equal to 3?     √3i x (-√3i) = 3

Guest Jan 6, 2015

Best Answer 

 #1
avatar+92749 
+10

$$i=\sqrt{-1}$$       It is an imaginary number.

 

$$i\times i = \sqrt{-1}\times \sqrt{-1} = -1$$

SO

 

√3i x (-√3i) 

 

$$\\=\sqrt3\times i\times -\sqrt3\times i\\
=-\sqrt3\times\sqrt3\times i\times i\\
=-\sqrt9\times i\times i\\
=-3\times -1\\
=3$$

Melody  Jan 7, 2015
 #1
avatar+92749 
+10
Best Answer

$$i=\sqrt{-1}$$       It is an imaginary number.

 

$$i\times i = \sqrt{-1}\times \sqrt{-1} = -1$$

SO

 

√3i x (-√3i) 

 

$$\\=\sqrt3\times i\times -\sqrt3\times i\\
=-\sqrt3\times\sqrt3\times i\times i\\
=-\sqrt9\times i\times i\\
=-3\times -1\\
=3$$

Melody  Jan 7, 2015

8 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.